2020
DOI: 10.1002/jor.24770
|View full text |Cite
|
Sign up to set email alerts
|

Changes in knee adduction moment wearing a variable‐stiffness shoe correlate with changes in pain and mechanically stimulated cartilage oligomeric matrix levels

Abstract: This study aimed to determine if changes in knee adduction moment (KAM) after 6 months of variable‐stiffness shoe wear are associated with changes in symptoms or serum levels of cartilage oligomeric matrix protein (COMP) following a mechanical stimulus in subjects with medial knee osteoarthritis (OA). Twenty‐five subjects were enrolled in the study and assigned a variable‐stiffness shoe, and 19 subjects completed the 6‐month follow‐up. At baseline and follow‐up subjects underwent gait analysis in control and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…Despite a majority of therapies displaying a null statistical KAM and KAAI reduction, the clinical usage of these treatment modalities could significantly improve the presenting symptoms and physical activity level without increasing the biomechanical magnitude; thus, improving the quality of life of patients with KOA. Although the results of this study suggested that wearing variable-stiffness shoes is not preferable for long-term KAM reduction, our current study explained that variable-stiffness shoes displayed a major advantage in reducing KAM for patients with increasing walking speed 68. At the same time, variable-stiffness shoes had relatively less discomfort than equipment such as LWI.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Despite a majority of therapies displaying a null statistical KAM and KAAI reduction, the clinical usage of these treatment modalities could significantly improve the presenting symptoms and physical activity level without increasing the biomechanical magnitude; thus, improving the quality of life of patients with KOA. Although the results of this study suggested that wearing variable-stiffness shoes is not preferable for long-term KAM reduction, our current study explained that variable-stiffness shoes displayed a major advantage in reducing KAM for patients with increasing walking speed 68. At the same time, variable-stiffness shoes had relatively less discomfort than equipment such as LWI.…”
Section: Discussioncontrasting
confidence: 57%
“…Although the results of this study suggested that wearing variable-stiffness shoes is not preferable for long-term KAM reduction, our current study explained that variable-stiffness shoes displayed a major advantage in reducing KAM for patients with increasing walking speed. 68 At the same time, variable-stiffness shoes had relatively less discomfort than equipment such as LWI. Since the studies included in this NMA mainly involves patients with medial KOA, the consolidated results would be more useful for such patients.…”
Section: Discussionmentioning
confidence: 99%
“…These data showed that early changes in gait mechanics following ACLR are associated with longer‐term clinical changes and that higher KAM may be an important mechanical marker of OA risk. Because elevated KAM can be reduced through interventions such as knee braces, footwear, 37 and gait modifications, 38,39 pathological elevations are also potentially reversible, and thus, we consider KAM to be a mechanical marker of “pre‐OA.” 3 …”
Section: Mri Ute‐t2* Mechanics and Patient‐reported Outcomes (Pros) In “Pre‐oa”mentioning
confidence: 99%
“…Erhart‐Hledik et al 42 demonstrated the utility of such a “stimulus–response” approach where measuring the within‐person change in serum biomarkers after walking for 30 minutes was shown to result in changes to serum levels of cartilage oligomeric matrix protein (COMP), a marker of cartilage turnover, that predicted cartilage thinning 5 years later. Furthermore, observations that the change in KAM wearing a load‐altering shoe correlated with changes to pain and mechanically stimulated serum COMP in patients with medial knee OA highlight a potential role for the stimulus–response approach in monitoring disease‐modifying therapies 37 …”
Section: Mri Ute‐t2* Mechanics and Biomarkers In “Pre‐oa”mentioning
confidence: 99%
“…This lack of established superiority has resulted in clinical guidelines not recommending the use of LWIs in the clinical management of knee OA (7,8). Despite some evidence supporting an association between the cross-sectional magnitudes of KAM and knee pain (9,10), as well as associations in changes in between these outcomes after an intervention (11,12), a major limitation of the clinical trials used to inform these guidelines is the likely inclusion of biomechanical non-responders to LWIs, who would subsequently be less likely to improve pain under a biomechanically-driven framework.…”
Section: Introductionmentioning
confidence: 99%